Bright on the Grey Sea: Utilizing the Xiang System to Creatively Consider the Potentials of Menglong in Film Poetry - Chen, Chen (Auckland University of Technology, 2018)
This practice-led, artistic thesis develops a corpus of three film poems using the Xiang system (a philosophical and aesthetic system adapted from Chinese poetry) as both the central creative strategy and methodology to heighten poetic thinking within practice. This approach becomes a mediator between film poetry and the researcher as a lyrically reflective practitioner. The project also explores menglong as an artistic and narrative device in communicating emotion, meaning and lyrical nuance. In exploring these phenomena, the thesis draws inspiration from the work of the Tang dynasty poet Shangyin Li. Significantly, it considers the potential application in film poetry of the restraint and delicacy that is indicative of the Xiang system.
Keywords: Film poetry; Chinese poetry; Yi Xiang; Li Shangyin; Short film making; Chinese artistic research